Memories of war on the urban fringe: The Great War and the Paris “zone” during the interwar years - James Cannon (Essays in French Literature and Culture, 2019)
Journalists and novelists of the interwar period often compared the outskirts of Paris, in particular the “zone”, to the battlefields of the Great War. For literary flâneurs, it was the zone’s topographical or social elements that were most suggestive of the Front. For avant- garde writers, the zone confirmed the existence of an unconscious death drive, originally posited by Freud in an attempt to understand the blood-letting of 1914-1918. The revolutionary Left was more concerned with renewing the zone’s pre-war political vocation to condemn bourgeois militarism and capitalism while energising the working classes. For a variety of reasons, the zone thus became a significant site of counter-memory at odds with official commemorations of the war that tended to glorify the sacrifice of French soldiers while ignoring their lived experience.